Artificial intelligence in healthcare: A Canadian context. Issue 1 (January 2020) - Kassam, Adam; Kassam, Naila
Artificial Intelligence (AI) is poised to revolutionize the way in which medicine is practiced and thereby transform how healthcare is delivered. While in its nascence in terms of medical applications, it is imperative that the healthcare community plays an active role in helping co-design platforms for the future. This article outlines the Canadian context of AI development by touching on its history and current utility. It also outlines the importance of capital investment, sustainable design, and how Canada has a unique opportunity to be a global leader in AI infrastructure development.